The Development of E-Student Worksheet on Environmental Pollution to Improve Critical Thinking Skills of Junior High School Students - Sri Wahyuni; Aris Singgih Budiarso; Pramudya Dwi Aristya Putra; Erlia Narulita; Lum’atul Khoirot Rizki (Jurnal Penelitian Pendidikan IPA, 2021)
This study purposed to develop an E-student worksheet on environmental pollution material to improve the critical thinking skills of junior high school students. E-student worksheet is an electronic-based student worksheet that utilizes the internet in its application. E-student worksheets can create various kinds of content, both visual and audiovisual, to train and assist students in finding concepts through the learning process. The development research method used a 4-D model, but only three stages were carried out: defining, designing, and developing. This research was conducted on seventh-grade students at SMPIT Al Ghozali Jember. The instruments used in this study were validation sheets, learning implementation sheets, critical thinking skills tests, and student response questionnaires. The results of this study indicated that the E-student worksheet had very valid criteria with a value of 94%. The implementation of learning showed very high criteria with a value of 92%. The effectiveness of learning had effective criteria with an average N-gain value of 0.70, and student responses had a good criterion, with a value of 77.3%. It can be concluded that the E-student worksheet on environmental pollution material could improve students' critical thinking skills in science learning in junior high school